Frequency of Portal Vein Thrombosis in Patients with Liver Cirrhosis (Journal of Fatima Jinnah Medical University, 2018)
Background: Chronic hepatitis C load in Pakistan is one of the highest in the world and is a cause of significant mortality mainly because of liver failure. Patient with advanced cirrhosis can develop Portal vein thrombosis (PVT) and is a really common complication. Local as well as systemic causes might play an important role in development of PVT. PVT is responsible for about 5 – 10% of overall cases of portal hypertension and its prevalence among cirrhotic patients ranges between 4.4 - 15%.Patients and Methods: This study was conducted in Department of Medicine at Combined Military Hospital Lahore from January to June 2015. In this study, 75 patients having liver cirrhosis were included in which 46 patients (61.33%) were males and 29 patients (38.67%) were females. All patients had Doppler Ultrasonography by same consultant radiologist for evidence of portal vein thrombosis.Results: Out of 75 patients registered in this study, 11 patients (14.67%) developed portal vein thrombosis. in which 7 patients (63.63%) were male while 4 patients (36.37%) were female. Out of these 6 had chronic hepatitis C (54.54%) and 4 (36.36%) had chronic hepatitis B.Conclusion: Portal vein thrombosis is frequent in patients with liver cirrhosis although it is not common in normal population.
Keywords: portal vein, thrombosis, liver cirrhosis